Virulence factors and biofilm forming ability of Staphyloccoccus species isolated from skeletal lesions of broiler chickens - Gustaw M. Szafraniec; Dorota Chrobak-Chmiel; Izabella Dolka; Krzysztof Adamczyk; Kamil Sułecki; Beata Dolka (Scientific Reports)
Abstract Lameness in poultry is a significant issue in modern meat production that adversely affects both animal welfare and economic outcomes due to poor leg health, reduced locomotor function, increased feed conversion ratios, and poor performance. Fast-growing broilers are particularly susceptible to lameness, with Staphylococcus being a major bacterial cause of skeletal infections. The aim of this study was to identify Staphylococcus species isolated from skeletal lesions in broiler chickens and to characterize the factors that facilitate such infections. Bacterial strains were isolated from 25 commercial broiler flocks in eastern Poland. The median prevalence of Staphylococcus in birds per flock was 60%. In total, 47% of the examined chickens and 88% of the examined flocks tested positive for Staphylococcus. The main bone sites affected by staphylococci were the femur (56.7%), femoral head (necrosis) (34.3%), hock joints (9.0%), femoral head (transient necrosis) (9.0%), tibiotarsus (7.5%), foot pads (dermatitis) (3.0%), and stifle (knee) joints (1.5%). Of all 93 Staphylococcus strains, 59% (55/93) were isolated from the femora. Twelve staphylococcal species were identified, all coagulase-negative, where Staphylococcus cohnii (24.7%) was the most prevalent species, followed by S. epidermidis (16.1%), S. hominis (15.1%), S. lentus (10.8%), S. saprophyticus (9.7%), S. chromogenes (8.6%), S. arlettae (4.3%), S. sciuri (4.3%), S. haemolyticus (2.2%), S. xylosus (2.2%), S. carnosus (1.1%), and S. gallinarum (1.1%). Eleven and six different staphylococcal species were implicated in the pathogenesis of femoral and tibiotarsal lesions, respectively. More than one Staphylococcus species was isolated from 47.8% of all Staphylococcus-positive chickens. Nearly all (97.8%) of coagulase-negative staphylococci isolates had biofilm-forming ability, but most of them were categorized as weak biofilm producers. The highest biofilm production was observed in the strains that caused femoral head osteonecrosis and footpad dermatitis. Staphylococcus chromogenes, S. lentus, and S. epidermidis exhibited the highest DNase and/or gelatinase activity. Despite the low prevalence of certain adhesin genes, the eno gene encoding laminin-binding protein was highly represented in staphylococci (75.3%). The study highlights the complex nature of coagulase-negative staphylococcal infections in poultry and underscores the need for further research into their virulence mechanisms and control strategies.